Abuse of Power and Self-Entrenchment as a State Response to the COVID-19 Outbreak: The Role of Parliaments, Courts and the People - Kouroutakis, Antonios (SSRN, 2021)
The World Health Organization, on March 11th, declared the novel coronavirus outbreak a pandemic and while the pandemic is still spreading, and some counties are affected more than others, governments have had to respond, given that SARS-CoV2(Covid-19) poses a serious public health threat. In their responses, governments have adopted emergency measures balancing public health with a plethora of rights such as freedom of movement, right to assembly and freedom to religion. In liberal constitutional theory, the norm is that during emergencies power is concentrated in the hands of the executive. Interestingly due to the nature of the pandemic, in some countries, such as in Hungary, parliamentary sessions were suspended, in others such as in Greece and the UK they were either under function or gone virtually via online platforms respectively. This limited function of the legislative body has grave implications on the quality of modern democracy as parliamentary scrutiny is restricted, ministerial accountability is distorted and most importantly the voice of the opposition does not have an appropriate forum to be heard. On the top of that, a well established stance of deference prevails in the judiciary weakening judicial review as an extra mechanism of protection to monitor the political process. Such constitutional circumstances may give rise to abuse of executive power and application of policies for self-serving purposes and self-entrenchment. For instance, the government may allocate funding in a way to favor its reelection. The aim of this paper it to examine legitimate and illegitimate executive self-entrenchment in times of emergency and identify the role of different institutions, to monitor and scrutinize executive emergency actions.
Keywords: Pandemocracy; Abuse of power; Self-entrenchment